The use of priorities on token-ring networks for multimedia traffic. - Bisdikian, C. (IEEE Network : the magazine of global information exchange)
The authors consider the transport of multimedia traffic on a token-ring LAN. In order to guarantee acceptable QoS for multimedia traffic, resource management is required to insure that sufficient capacity from all shared resources is allocated to the priority traffic. Once a multimedia session is accepted and resources have been allocated, the next task is to insure that the high priority multimedia traffic actually obtains the resources which have been allocated to it